A New Approach to Stopping Viral Infections: Intestinal Tract as The Main Important Reservoir of Viruses Hidden in Carriers After Overcoming Infections - Zajac, Vladimir (British Journal of Healthcare and Medical Research, 2024)
Viruses are parasites. However, this basic fact is not accepted by most experts, virologists. This attitude is a disregard for the fact that a virus is a parasite that cannot exist on its own and is completely dependent on its carrier. This is the basic condition of its existence. The host of the parasite is a living cell. Which living cells are carriers of viruses